Simultaneous Catalytic Oxidation of a Lean Mixture of CO-CH4 over Spinel Type Cobalt Based Oxides - Neha Neha; Ram prasad; Satya Vir Singh (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2020)
A series of nickel-cobalt bimetal oxides in varying molar ratios and its single metal oxides were synthesized by reactive calcination of coprecipitated basic-carbonates. Several characterization techniques, such as: Bruneuer Emmett Teller (BET), X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Fourier Transform Infra Red (FTIR), and Hydrogen Temperature Programmed Reduction (H2-TPR), were performed over the oxides. Activities of oxides were evaluated in methane total oxidation in the presence or the absence of CO. The best catalytic performance was observed over NiCo catalyst with a Ni/Co molar ratio of 1:1, and the complete conversion of CO-CH4 mixture was achieved at 390 °C. Moreover, the presence of carbon monoxide improves CH4 total oxidation over nickel-cobalt mixed oxides. Structural analysis reveals that the insertion of nickel into the spinel lattice of cobalt oxide causes the structural disorder, which probably caused the increase of the amount of octahedrally coordinated divalent nickel cations that are responsible for catalytic activity. Stability of the best-performed catalyst has been tested in the two conditions, showing remarkable long-term stability and thermal stability, however, showed deactivation after thermally ageing at 700 °C. Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).